STUDY OF SOIL STRATIFICATION IN LANDSLIDE AREAS ON BANTUAS ROAD USING THE RESISTIVITY GEOELECTRIC METHOD - Haryono, Arif; Supriyanto, Supriyanto; Djayus, Djayus; Mislan, Mislan; Lepong, Piter; Abbas, Asri Yana Pratama (Indonesian Physical Review, 2024)
A landslide is a natural disaster that often occurs in the Palaran sub-district, Samarinda, East Kalimantan. This sub-district with an area of ​​221.29 km2 is considered strategic as a buffer area for the National Capital City (IKN). Construction of toll roads, ports, factories, and housing has begun to be carried out here. However, in Palaran there are still many roads damaged due to landslides, one of which is Bantuas Road. To study soil stratification on the Bantuas Road section, research has been carried out using the dipole-dipole configuration of the resistivity geoelectric method. The data acquisition process was carried out at two locations, namely at the first landslide (STA 7+150) and the second landslide (STA 9+450), with each location consisting of three lines. The data processing uses Res2Dinv software to produce a two-dimensional model. Based on the resulting model, it is known that the landslide area at STA 7+150 is at a distance of 48 to 96 meters with the slip area at a depth of around 11 to 12 meters. Meanwhile, at STA 9+450, the landslide area occurred at a distance of 48 to 80 meters with the slip area at a depth of 8 to 10 meters. The slip area in the first landslide is interpreted to have occurred at the contact area between unconsolidated material and dense sand, while in the second landslide, it occurred at the contact area between weak silty sand and dense sandy clay.